Robust Vehicle Sideslip Estimation Based on Kinematic Considerations. Issue 1 (July 2017) - Selmanaj, D.; Corno, M.; Panzani, G.; Savaresi, S.M.
Abstract: - This paper proposes an inertial measurement based sideslip angle estimation for automotive applications. Measuring sideslip angle is costly; in most cases, in most case estimation is a preferred choice. Most estimation solutions are based on dynamical models of the car. To properly work, these solutions need to also estimate the road friction. This increases their complexity and affects their robustness. The present study proposes an inertial based approach that does not require the knowledge nor the estimation of road friction. This considerably simplifies the design, tuning and validation of the approach. Focus is devoted to the study of the effect of measurement errors. An extensive experimental validation confirms that the estimate is accurate and robust to a wide range of driving scenarios.